Force-extension curves for broken-rod macromolecules: Dramatic effects of different probing methods for two and three rods - Alexeev, A. V.; Maltseva, D. V.; Ivanov, V. A.; Klushin, L. I.; Skvortsov, A. M. (The Journal of chemical physics, 2015)
We study force-extension curves of a single semiflexible chain consisting of several rigid rods connected by flexible spacers. The atomic force microscopy and laser optical or magnetic tweezers apparatus stretching these rod-coil macromolecules are discussed. In addition, the stretching by external isotropic force is analyzed. The main attention is focused on computer simulation and analytical results. We demonstrate that the force-extension curves for rod-coil chains composed of two or three rods of equal length differ not only quantitatively but also qualitatively in different probe methods. These curves have an anomalous shape for a chain of two rods. End-to-end distributions of rod-coil chains are calculated by Monte Carlo method and compared with analytical equations. The influence of the spacer’s length on the force-extension curves in different probe methods is analyzed. The results can be useful for interpreting experiments on the stretching of rod-coil block-copolymers.